Editorial: perception and cognition: interactions in the ageing brain - Allen, Harriet A.; Roberts, Katherine Leonie (Frontiers Media, 2016)
Healthy ageing can lead to declines in both perceptual and cognitive functions. Many of the studies in this Topic demonstrate such age-related declines, but also identify links between them. Encouragingly, these links suggest that improving perception could benefit cognition. In addition, while compensatory cognitive strategies were mainly unsuccessful in improving perception, cognitive training was effective under certain conditions